Systematic review and meta-analysis of metacestode prevalence in small ruminants in Ethiopia - Asmare, K.; Sibhat, B.; Abera, M.; Haile, Aynalem; Degefu, H.; Fentie, T.; Bekele, J.; Terefe, G.; Szonyi, Barbara; Robertson, L.J.; Wieland, Barbara (Elsevier, 2016)
Metacestode, larval stages of canid cestode parasites are among the causes of morbidity, mortality and financial losses in small ruminants in Ethiopia as a result of organ and carcass condemnation at slaughter. Several studies have been conducted over the years; however, these studies often had limited scope and coverage. This systematic review and meta-analysis was conducted to collate the information so far available in order to provide a pooled prevalence estimate at national level and identify potential predictors. Published and gray literature written in English and Amharic during the period between, 1st of January, 1990 and June 25, 2015 were searched from electronic databases and repositories of academic and research institutions. Relevant animal level data on 67,743 small ruminants was extracted from 23 published articles and one master’s thesis resulting altogether in 86 animal level reports that conformed to predefined criteria. The dataset was analyzed using a meta-analytical approach. The pooled prevalence estimate computed for metacestodes infection was 11.8% with a 95% confidence interval (CI) of 9.0, 15.2. The highest prevalence estimate 31.2% (95% CI: 23.1, 40.9) was found for Cysticercus tenuicollis (Taenia hydatigena) followed by cystic echinococcosis (Echinococcus granulosus) 8.8% (95% CI: 5.8, 13.1), Cysticercus ovis(Taenia ovis) 4.9% (95% CI: 2.9, 9.4) and Coenurus cerebralis (Taenia multiceps) 4.6% (95% CI: 1.6, 12.2). Among the predictors considered for heterogeneity analysis only sample size and metacestode type fitted the final multivariable meta-regression model and explained 26.3% of the explainable heterogeneity between studies (p<0.05). The prevalence was noted to decrease with increasing sample size. No significant difference in prevalence was observed between sheep and goats (p>0.05). In conclusion, this review showed a widespread occurrence of metacestodes in small ruminants in Ethiopia. Thus, a holistic approach to break the life cycle of these parasitic stages is suggested, including regulatory interventions that encourage dog owners to keep their dogs confined and prevent backyard slaughter and proper management of abattoir waste disposal.